THE IMPACT OF LOGISTICS CAPABILITIES ON 3PL PROVIDER FIRM PERFORMANCE - Yanpiboon, Tanyanart (RMUTT Global Business and Economics Review, 2025)
This research investigates the impact of logistics capabilities on firm performance in third-party logistics (3PL) providers. Drawing on the resource-based view, the researchers examine how three key capability dimensions—service capability, innovation capability, and flexible capability—influence both service and financial performance outcomes. Using SMART PLS 4.0 with data collected from 205 3PL firms in Thailand, the research reveals that all three capability dimensions significantly enhance service performance, with flexible capability demonstrating the strongest effect. Innovation capability uniquely contributes directly to both service and financial performance, while service and flexible capabilities influence financial outcomes primarily through service performance. The findings validate the service-profit chain framework in logistics contexts and highlight innovation capability as a valuable strategic resource generating dual benefits. This research advances the theoretical understanding of capability-performance linkages in logistics outsourcing while providing practical insights for 3PL providers seeking to prioritize capability investments for competitive advantage. By distinguishing between direct and indirect performance effects across capability dimensions, the study offers a more nuanced perspective on how logistics capabilities translate into measurable performance outcomes in increasingly complex supply chain environments.